2012
DOI: 10.1152/ajpregu.00010.2012
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular output and aortic blood flow in response to changes in preload and afterload in the preterm piglet heart

Abstract: Low systemic blood flow occurs in up to 30% of infants born at less than 30 wk gestation. It is associated with increased morbidity and mortality, and current treatments are ineffective in 40% of cases. The aim of this study was to assess the ability of the preterm heart to respond to the acute shifts in preload and afterload that occur at the time of birth. Myocardial and coronary vascular function was assessed using an isolated working heart model in term (115 days) and preterm (92 days) piglets. Cardiac out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…However, in 1993, Gill and Weindling24 showed significantly reduced shortening fraction during the first 24 h after birth in a population comparable to ours. It has been demonstrated that the immature myocardium of the newborn is more sensitive to changes in afterload than the more mature heart 18 25. We therefore speculate that the significant reduction in LV myocardial velocities from 5 to 12 h may represent a transitional response to the postnatal increase in afterload.…”
Section: Discussionmentioning
confidence: 78%
“…However, in 1993, Gill and Weindling24 showed significantly reduced shortening fraction during the first 24 h after birth in a population comparable to ours. It has been demonstrated that the immature myocardium of the newborn is more sensitive to changes in afterload than the more mature heart 18 25. We therefore speculate that the significant reduction in LV myocardial velocities from 5 to 12 h may represent a transitional response to the postnatal increase in afterload.…”
Section: Discussionmentioning
confidence: 78%
“…The preterm heart, however, may not have the functional capacity to acutely adapt to increased afterload, as suggested in a recently reported piglet model. 39 …”
Section: Systolic Function Of the Preterm Heartmentioning
confidence: 99%
“…In support of the latter, recent investigations in isolated preterm piglet hearts suggest that the preterm heart may have better ''preload reserve,'' and thus cardiac output may be augmented best through increased preload. 39 Further translational and clinical work is necessary to investigate the limits of diastolic reserve of the immature myocardium and optimal strategies to augment cardiac output in the preterm heart.…”
Section: Clinical Relevance Of Preterm Myocardial Functionmentioning
confidence: 99%
“…The effect of high airway pressure is not limited to the pulmonary vasculature, with direct compressive effects observed on the newborn heart, resulting in reduced cardiac performance and ventricular output (21,24). This is further complicated by recent studies in preterm animals (25,26) and preterm infants (27,28) demonstrating that the preterm heart, particularly the myocardium, is structurally immature, translating to lower contractility in the days after birth and an inability to cope with increasing afterload.…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%